FRUCTOSANS AND PHENOLIC COMPOUNDS OF YACON - M. S. Gins; V. K. Gins; P. F. Kononkov; A. A. Dunich; A. V. Daschenko; L. T. Mischenko (Овощи России, 2015)
Using the high-efficiency liquid chromatography, the phenolic compounds of yacon (Polymnia sonchifolia) introduced in Ukraine have been studied. The derivants of hydroxycinnamic acid is prevalent in the ethanol extracts from leaves and roots of yacon. Differences in the contents of  ethanol extracts from fresh and dry roots were shown. The total amount of hydroxycinnamic acids was 2,8 % – 4,3 % depending on the layer of leaves. It was found that roots content 36-45% of fructosans expressed as fructose and dry matter.